Jean-Martin Charcot: the polymath - Camargo, Carlos Henrique Ferreira; Coutinho, Léo; Neto, Ylmar Correa; Engelhardt, Eliasz; Filho, Pericles Maranhão; Walusinski, Olivier; Teive, Hélio Afonso Ghizoni (Arquivos de Neuro-Psiquiatria, 2023)
Jean-Martin Charcot, widely regarded as a leading founder of modern neurology, made substantial contributions to the understanding and characterization of numerous medical conditions. His initial focus was on internal medicine, later expanding to include neuropathology, general neurology, and eventually emerging fields such as neuropsychology and neuropsychiatry. Furthermore, Charcot's intellectual pursuits extended beyond medicine, encompassing research in art history, medical iconography, sociology, religious studies, and the arts, solidifying his status as a polymath.
Keywords: History; Neurology; Neuropathology; Internal Medicine; Psychiatry; Psychology; Polymath